2010
DOI: 10.1001/archgenpsychiatry.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Similar White Matter Aberrations in Children With Autism and Their Unaffected Siblings

Abstract: Our findings suggest that white matter structure may represent a marker of genetic risk for autism or vulnerability to development of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
128
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 98 publications
(113 reference statements)
16
128
1
2
Order By: Relevance
“…10 Moreover, several DTI studies also have revealed abnormalities of the left superior longitudinal fasciculus in ASD. 17,20,23,41,44 Although the important role the left superior longitudinal fasciculus has in language processing has been known since the 19th century, the importance of this structure in the right hemisphere is emerging. Abnormalities of the right superior longitudinal fasciculus also have important implications for ASD due to its connection to the superior temporal sulcus, 42 a region well known for its role in processing biologic motion, which is abnormal in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Moreover, several DTI studies also have revealed abnormalities of the left superior longitudinal fasciculus in ASD. 17,20,23,41,44 Although the important role the left superior longitudinal fasciculus has in language processing has been known since the 19th century, the importance of this structure in the right hemisphere is emerging. Abnormalities of the right superior longitudinal fasciculus also have important implications for ASD due to its connection to the superior temporal sulcus, 42 a region well known for its role in processing biologic motion, which is abnormal in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…45 Moreover, several DTI studies have revealed abnormalities of the right superior longitudinal fasciculus. 17,[20][21][22]46 Finally, similar to the inferior fronto-oc- cipital fasciculus, the superior longitudinal fasciculus also has a broad neuroanatomic extent, connecting the frontal, parietal, and temporal lobes. 42 As evident in Fig 1, this tract also may potentially serve an important role in linking all the components of brain structures involved in social cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While multiple white matter structures have been found to be affected in ASD (for a review, see Aoki et al, 2013;Barnea-Golary et al, 2004;Barnea-Golary et al, 2010;Olson et al, 2015), the left uncinate may be particularly important in processing socio-affective information (Pehrs et al, 2015;Olson et al, 2015). There seems to be a relatively left dominant abnormality in the uncinate fasciculus in ASD.…”
Section: Potential Neural Correlates Of Socio-affective Deficits In Amentioning
confidence: 99%